Angiogenic Potential of Various Oral Cavity–Derived Mesenchymal Stem Cells and Cell-Derived Secretome: A Systematic Review and Meta-Analysis - Shekatkar, Madhura; Kheur, Supriya; Deshpande, Shantanu; Sanap, Avinash; Kharat, Avinash; Navalakha, Shivani; Gupta, Archana; Kheur, Mohit; Bhonde, Ramesh; Merchant, Yash P. (European Journal of Dentistry, 2023)
Recent evidence suggests the immense potential of human mesenchymal stem cell (hMSC) secretome conditioned medium-mediated augmentation of angiogenesis. However, angiogenesis potential varies from source and origin. The hMSCs derived from the oral cavity share an exceptional quality due to their origin from a hypoxic environment. Our systematic review aimed to compare the mesenchymal stem cells (MSCs) derived from various oral cavity sources and cell-derived secretomes, and evaluate their angiogenic potential. A literature search was conducted using PubMed and Scopus from January 2000 to September 2020. Source-wise outcomes were systematically analyzed using in vitro, in vivo, and in ovo studies, emphasizing endothelial cell migration, tube formation, and blood vessel formation. Ninety-four studies were included in the systematic review, out of which 4 studies were subsequently included in the meta-analysis. Prominent growth factors and other bioactive components implicated in improving angiogenesis were included in the respective studies. The findings suggest that oral tissues are a rich source of hMSCs. The meta-analysis revealed a positive correlation between dental pulp–derived MSCs (DPMSCs) and stem cells derived from apical papilla (SCAP) compared to human umbilical cord–derived endothelial cell lines as a control. It shows a statistically significant positive correlation between the co-culture of human umbilical vein endothelial cells (HUVECs) and DPMSCs with tubule length formation and total branching points. Our meta-analysis revealed that oral-derived MSCs (dental pulp stem cells and SCAP) carry a better angiogenic potential in vitro than endothelial cell lines alone. The reviewed literature illustrates that oral cavity–derived MSCs (OC-MSCs) increased angiogenesis. The present literature reveals a dearth of investigations involving sources other than dental pulp. Even though OC-MSCs have revealed more significant potential than other MSCs, more comprehensive, target-oriented interinstitutional prospective studies are warranted to determine whether oral cavity–derived stem cells are the most excellent sources of significant angiogenic potential.
Keywords: secretome; angiogenesis; angiogenic growth factors; cytokine analysis